Complexity and social work - van Ewijk, Hans, ....- (Abingdon, Oxon ; : Routledge, 2018)
Being socially competent is essential in late modern society. We expect people to find their own accommodation, partner, job, community, and lifestyle and struggle to find answers for those who are not able or do not have the opportunity to achieve these things. By placing social complexity, social vulnerability and social-efficacy within a framework of social policy and social practice, Complexity and Social Work argues that growing social complexity excludes more and more citizens from social participation. The book starts with exploring complexity, super-diversity, vulnerability and social efficacy. From there the book deals with the discourses of social policy, social work and social work research, pledging for social policy aiming at desired outcomes, for generic contextual social work, and for a research practice that recognizes practical wisdom. Aimed at final year undergraduate, postgraduates, professionals, trainers and lecturers involved in social work, social policy, social care, mental health and allied fields who are committed to treating socially vulnerable people with respect and acceptance, this book, the first of its kind, offers new perspectives on social complexity for practice, theory and research in human services.
Translation of: Omgaan met sociale complexiteit.
Includes bibliographical references.
Keywords: Interpersonal relations; Social policy; Social problems; Social service